The Latin American Epidemiology Network for ALS (Laenals). Issue 5 (3rd July 2022) - Hardiman, Orla; Heverin, Mark; Rooney, James; Lillo, Patricia; Godoy, Gladys; Sáez, David; Valenzuela, Daniel; Hughes, Ricardo; Perna, Abayuba; Ketzoian, Carlos N.; Vazquez, Cristina; Gutierrez Gil, Joel; et al.
Abstract: Background: There is evolving evidence of non-uniform distribution of ALS worldwide, with apparently lower incident and prevalent rates outside populations of European origin. However, the phenotype, survival and environmental risk in populations of mixed ancestral origin have not been well established. Large scale population based studies of incidence, prevalence, phenotype and risk factors in admixed populations are necessary to determine the true demography of ALS, and to test the hypothesis of differential risk and phenotype in populations of mixed ancestry. Methods: The Latin American Epidemiological Network of ALS (LAENALS) has been established to perform a comparative analysis of ALS epidemiology between three different Latin American populations (Cuba, Uruguay and Chile), and to test the hypothesis that the demographics, phenotype and outcome of ALS are influenced by ancestral origin, and that environmental and occupational risk factors differ across different ethnicities due to subtle differences in gene- environmental interactions. Recognition and interrogation of these differences is an important step toward novel therapeutic approaches and personalized medicine for all ALS both in the US, and worldwide. Discussion: This work will enable direct and detailed comparative studies between different ancestral populations with varying degrees of admixture, with facility for comparison with a large European reference dataset for ALS, and will provide a unique and rich dataset of admixed populations for later comparative genomic studies.